2012
DOI: 10.3897/zookeys.178.1410
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the strongly rheophilous tadpoles of Malagasy tree frogs, genus Boophis (Anura, Mantellidae), and identification of new candidate species via larval DNA sequence and morphology

Abstract: This study provides detailed morphological descriptions of previously unknown tadpoles of the treefrog genus Boophis Tschudi and analyses of habitat preferences of several of these tadpoles in Ranomafana National Park. A total of twenty-two tadpoles determined via DNA barcoding are characterized morphologically herein, fourteen of them for the first time. Twelve of these tadpoles belong to taxonomically undescribed candidate species which in several cases are so far only known from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In the meantime, about 32 of these have been formally described as new species, or resurrected from synonymy (e.g., Glaw et al, 2010;Köhler et al, 2010;Vences et al, 2010), and additional species have been newly discovered and described; the number of nominal species of native amphibians in Madagascar has consequently risen to 292. During this same time, various studies have revealed 22 additional, previously unknown genetic lineages qualifying as candidate species: one Anodonthyla , one Stumpffia , one Blommersia, two Boophis and one Guibemantis (Gehring et al, 2010), four Mantidactylus (Randrianiaina et al, 2011), and 12 Boophis (Randrianiaina et al, 2012). The COI data herein, mostly from our own expeditions into northern Madagascar (Makira and Tsaratanana areas) in 2009 and 2010, provide evidence for the presence of at least 14 further candidate species with divergences to nominal taxa above the threshold of 6% uncorrected pairwise COI distance (further discoveries from two other surveys in 2010 and 2012 are not yet analyzed): two Boophis, two Cophyla, one Gephyromantis, one Guibemantis, three Rhombophryne, two Spinomantis and three Stumpfßa.…”
Section: Discussionmentioning
confidence: 97%
“…In the meantime, about 32 of these have been formally described as new species, or resurrected from synonymy (e.g., Glaw et al, 2010;Köhler et al, 2010;Vences et al, 2010), and additional species have been newly discovered and described; the number of nominal species of native amphibians in Madagascar has consequently risen to 292. During this same time, various studies have revealed 22 additional, previously unknown genetic lineages qualifying as candidate species: one Anodonthyla , one Stumpffia , one Blommersia, two Boophis and one Guibemantis (Gehring et al, 2010), four Mantidactylus (Randrianiaina et al, 2011), and 12 Boophis (Randrianiaina et al, 2012). The COI data herein, mostly from our own expeditions into northern Madagascar (Makira and Tsaratanana areas) in 2009 and 2010, provide evidence for the presence of at least 14 further candidate species with divergences to nominal taxa above the threshold of 6% uncorrected pairwise COI distance (further discoveries from two other surveys in 2010 and 2012 are not yet analyzed): two Boophis, two Cophyla, one Gephyromantis, one Guibemantis, three Rhombophryne, two Spinomantis and three Stumpfßa.…”
Section: Discussionmentioning
confidence: 97%
“…In Madagascan tadpoles, some closely related groups indeed show a broader range of traits than others which is not necessarily linked to their species richness (e.g., [ 80 82 ]). There are several accounts of homoplasy in morpho-functional traits in Madagascan tadpoles [ 83 ] although in general, tadpole morphology largely fits phylogeny ([ 84 ] and references cited above). As the mentioned exceptions are randomly distributed between the taxonomic groups included in this study, they may not necessarily have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Suctorial tadpoles of various frog lineages have conquered torrential habitats independently (Gradwell 1973;Altig and Johnston 1989;McCranie et al 1989;Haas and Richards 1998;McDiarmid and Altig 1999;Coloma 2002;Matsui et al 2005;Pramuk and Lehr 2005;Shimada et al 2011;Randrianiaina et al 2012;Zachariah et al 2012). These suctorial tadpoles have evolved certain morphological features convergently.…”
Section: Discussionmentioning
confidence: 99%